Electric-arc welding flux-cored wire based on C4 steel and preparation method of electric-arc welding flux-cored wire

By using fluorine-doped graphene aerogel and other constituent materials in arc welding flux cored welding wire, the problem of unstable welding quality when welding C4 steel is solved, and the welding strength and corrosion resistance are significantly improved.

CN119407396AActive Publication Date: 2025-02-11JIANGSU JIUZHOU NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411426160.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-11
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

When welding C4 steel, the welding quality of traditional arc welding flux core welding wire is unstable, resulting in insufficient strength of the welded joint and poor corrosion resistance.

Method used

Arc welding flux core welding wire based on C4 steel, which includes a wire coating and wire powder, by doping microcarbon ferrochromium, low-carbon ferromanganese, nickel powder, molybdenum powder, fluorine-doped graphene aerogel, titanium dioxide, Ferrosilicon, magnesium oxide, yttrium oxide and iron powder are fully stirred, wet ball milling and drying to obtain welding wire powder, and fill it into U-shaped steel strip, rolling, drawing and coiling, forming arc welding flux core welding wire .

Benefits of technology

It significantly improves the tensile strength and toughness of the welding area, enhances the mechanical properties and corrosion resistance of the C4 steel parts after welding, improves the overall quality of the welding area, and extends the fatigue life and damage resistance of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of flux-cored wires, in particular to an electric-arc welding flux-cored wire based on C4 steel and a preparation method of the electric-arc welding flux-cored wire, and aims to solve the problems that an existing electric-arc welding flux-cored wire for the C4 steel is often unstable in welding quality, so that the strength of a welded joint is insufficient, and the corrosion resistance is poor. According to the preparation method, the fluorine-doped graphene aerogel serves as an important component of the arc welding flux-cored wire, so that the pore defect rate and the crack generation probability in the welding process can be effectively reduced, and the tensile strength and toughness of a welding area can be remarkably improved; according to the electric-arc welding flux-cored wire, the welded C4 steel part has more excellent mechanical performance and corrosion resistance, the overall quality of a welding area is improved, the overall fatigue life of the structure is prolonged, the damage resistance of the structure is improved, the electric-arc welding flux-cored wire is suitable for various welding technologies, the requirements under different welding conditions can be met, the technology is simple, operation is easy, and popularization is easy. The method is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flux-cored welding wires, and in particular to an arc welding flux-cored welding wire based on C4 steel and a preparation method thereof. Background Art

[0002] With the development of modern industry, high-strength steel plays an increasingly important role in the fields of construction, transportation, energy, etc. As a high-strength steel, C4 steel is widely used in aerospace, petrochemical, marine engineering and other fields. However, due to its high strength and special chemical composition, traditional arc welding flux-cored wire often has unstable welding quality when welding C4 steel, resulting in insufficient strength of the welded joint and poor corrosion resistance. It is often difficult to meet the requirements of high strength and good welding processability at the same time.

[0003] Therefore, developing an arc welding flux-cored wire based on C4 steel and a preparation method thereof is of great significance for improving the welding quality of C4 steel. Summary of the invention

[0004] In order to overcome the above-mentioned technical problems, the object of the present invention is to provide an arc welding flux-cored wire based on C4 steel and a preparation method thereof: micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, fluorine-doped graphene aerogel, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder are fully stirred, and then wet-milled and dried to obtain welding wire powder, and the C4 steel strip E304L steel strip is rolled to form a U-shaped steel strip, and then the welding wire powder is filled into the U-shaped steel strip, and then the U-shaped steel strip is rolled and closed to form an O-shaped filling steel wire, and then the O-shaped filling steel wire is drawn, and then coiled and packaged to obtain an arc welding flux-cored wire based on C4 steel, which solves the problem that the existing arc welding flux-cored wire for C4 steel often has unstable welding quality, resulting in insufficient strength of the welding joint and poor corrosion resistance.

[0005] The purpose of the present invention can be achieved through the following technical solutions: An arc welding flux-cored wire based on C4 steel, comprising a welding wire coating layer and welding wire powder; The welding wire coating layer is a C4 steel strip E304L steel strip with a thickness of 0.3 mm; The mass of the welding wire powder is 28% of the mass of the arc welding flux-cored wire based on C4 steel; Wherein, the welding wire powder comprises the following components in parts by weight: 35-40 parts of micro-carbon ferrochrome, 8-12 parts of low-carbon ferromanganese, 7.5-11.5 parts of nickel powder, 5-9 parts of molybdenum powder, 2.5-9.5 parts of fluorine-doped graphene aerogel, 4-8 parts of titanium dioxide, 5-13 parts of ferrosilicon, 1-3 parts of magnesium oxide, 1-3 parts of yttrium oxide and 22-36 parts of iron powder; Wherein, the fluorine-doped graphene aerogel is prepared by the following steps: Step s1: adding flake graphite, concentrated sulfuric acid and sodium nitrate to a three-necked flask equipped with an agitator and a thermometer, stirring the reaction at a temperature of -5-0°C and a stirring rate of 300-400r / min for 20-30min, then adding potassium permanganate and continuing to stir the reaction for 1.5-2.5h, then heating to 35-40°C and continuing to stir the reaction for 2-3h, then adding deionized water and continuing to stir the reaction for 10-12min, then heating to 95-100°C and continuing to stir the reaction for 1-2h, after the reaction is completed, the reaction product is cooled to room temperature, then hydrogen peroxide solution is added, then allowed to stand for 2-3h, then centrifuged, the precipitate is washed with distilled water for 3-5 times in sequence, then placed in a vacuum drying oven, and dried at a temperature of 50-55°C for 3-5h to obtain graphene oxide; Step s2: adding graphene oxide and deionized water to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersing for 40-50 minutes at an ultrasonic frequency of 35-45kHz, then adding ascorbic acid and stirring the mixture for 3-5 hours at a temperature of 0-5°C and a stirring rate of 300-400r / min, then heating the mixture to reflux and continuing to stir the mixture for 10-15 hours, centrifuging the reaction product after the reaction is completed, and immersing the precipitate in distilled water for 72-96 hours, and then freeze-drying the mixture to obtain graphene aerogel; Step s3: Add graphene aerogel and hydrofluoric acid into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 20-30 minutes at a temperature of -5-0°C and a stirring rate of 300-400r / min, then raise the temperature to reflux and continue stirring and reacting for 20-25 hours. After the reaction is completed, centrifuge the reaction product, immerse the precipitate in distilled water for 20-30 hours, and then freeze-dry to obtain fluorine-doped graphene aerogel.

[0006] As a further solution of the present invention: the usage ratio of the flake graphite, concentrated sulfuric acid, sodium nitrate, potassium permanganate, deionized water and hydrogen peroxide solution in step s1 is 3g:80-90mL:2-3g:12-16g:120-150mL:15-20mL.

[0007] As a further solution of the present invention: the mass fraction of the concentrated sulfuric acid in step s1 is 98%; the mass fraction of the hydrogen peroxide solution is 30%.

[0008] As a further solution of the present invention: the usage ratio of the graphene oxide, deionized water and ascorbic acid in step s2 is 0.1-0.5 g: 100-120 mL: 0.3-0.9 g.

[0009] As a further solution of the present invention: the usage ratio of the graphene aerogel and hydrofluoric acid in step s3 is 0.1-0.5 g: 10-12 mL.

[0010] As a further solution of the present invention: the mass fraction of the hydrofluoric acid in step s3 is 10-15%.

[0011] As a further solution of the present invention: a method for preparing an arc welding flux-cored wire based on C4 steel comprises the following steps: Step 1: Weigh 35-40 parts of low-carbon ferrochrome, 8-12 parts of low-carbon ferromanganese, 7.5-11.5 parts of nickel powder, 5-9 parts of molybdenum powder, 2.5-9.5 parts of fluorine-doped graphene aerogel, 4-8 parts of titanium dioxide, 5-13 parts of ferrosilicon, 1-3 parts of magnesium oxide, 1-3 parts of yttrium oxide and 22-36 parts of iron powder according to weight parts, and set aside; Step 2: fully stir micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, fluorine-doped graphene aerogel, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder, then wet-mill them, and then place them in a vacuum drying oven and dry them at a temperature of 130-150° C. for 3-5 hours to obtain welding wire powder; Step 3: Roll the C4 steel strip and E304L steel strip to form a U-shaped steel strip, then fill the welding wire powder into the U-shaped steel strip, then roll the U-shaped steel strip closed to form an O-shaped filling steel wire, then draw the O-shaped filling steel wire until the diameter is 1.4 mm, then coil and package to obtain an arc welding flux-cored wire based on C4 steel.

[0012] Beneficial effects of the present invention: The invention discloses an arc welding flux-cored welding wire based on C4 steel and a preparation method thereof. The method comprises the following steps: fully stirring micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, fluorine-doped graphene aerogel, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder, and then wet-milling and drying to obtain welding wire powder; rolling a C4 steel strip and an E304L steel strip to form a U-shaped steel strip; then filling the welding wire powder into the U-shaped steel strip; then rolling the U-shaped steel strip closed to form an O-shaped filled steel wire; then drawing the O-shaped filled steel wire; and then rolling and packaging to obtain an arc welding flux-cored welding wire based on C4 steel. Wire; the preparation method uses fluorine-doped graphene aerogel as an important component of arc welding flux-cored wire, which can not only effectively reduce the porosity defect rate and crack generation probability during welding, but also significantly improve the tensile strength and toughness of the welding area, so that the welded C4 steel parts have more excellent mechanical properties and corrosion resistance, improve the overall quality of the welding area, and thus improve the fatigue life and damage resistance of the entire structure. The arc welding flux-cored wire is suitable for various welding processes, can meet the needs under different welding conditions, and has a simple process, easy operation, and is suitable for large-scale production.

[0013] In the process of preparing arc welding flux-cored wire based on C4 steel, a fluorine-doped graphene aerogel is first prepared. First, graphene oxide is prepared using flake graphite as a raw material. Then, graphene oxide is used as a raw material, ascorbic acid is added as a reducing agent, and the graphene aerogel is prepared by combining hydrothermal reaction and freeze-drying method. Finally, the graphene aerogel is fluorinated with hydrofluoric acid, and a large amount of fluorine element is introduced into the graphene aerogel to obtain fluorine-doped graphene aerogel. The fluorine-doped graphene aerogel has the advantages of stable properties of graphene, high electrical conductivity, good thermal conductivity, and high mechanical strength. After adding it to the arc welding flux-cored wire, the mechanical strength and high-temperature stability of the arc welding flux-cored wire can be greatly improved. At the same time, it has an extremely high pore structure and specific surface area. When participating in the welding process, the pore structure is also welded. The flow of the molten pool provides a good channel, promotes the discharge of slag and the formation of the weld, and will undergo complex physical and chemical reactions with the deposited metal to form a strong metallurgical bond, which not only enhances the density and strength of the deposited metal, improves its toughness and fatigue resistance, but also makes the weld appearance smoother and flatter. After doping with fluorine, fluorine can react with oxygen to form volatile fluorides, effectively removing oxygen from the weld and preventing oxidation and embrittlement of the weld. The residual fluorine will also form a strong chemical bond with the carbon atoms in the graphene, forming a physical barrier on the surface of the deposited metal, hindering the penetration of corrosive media (such as water, oxygen, acid, alkali, etc.) into the interior, reducing their contact with the metal matrix of the welding wire, thereby slowing down the occurrence of corrosion, thereby significantly improving the corrosion resistance of the flux-cored welding wire. DETAILED DESCRIPTION

[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] Embodiment 1: This embodiment is a method for preparing an arc welding flux-cored wire based on C4 steel, comprising the following steps: Step S11: 3g of flake graphite, 80mL of concentrated sulfuric acid with a mass fraction of 98% and 2g of sodium nitrate are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of -5°C and a stirring rate of 300r / min for 20min, then 12g of potassium permanganate is added and the stirring reaction is continued for 1.5h, then the temperature is raised to 35°C and the stirring reaction is continued for 2h, then 120mL of deionized water is added and the stirring reaction is continued for 10min, then the temperature is raised to 95°C and the stirring reaction is continued for 1h, after the reaction is completed, the reaction product is cooled to room temperature, and then 15mL of a hydrogen peroxide solution with a mass fraction of 30% is added, and then it is allowed to stand for 2h, and then centrifuged, and the precipitate is washed with distilled water three times in sequence, and then placed in a vacuum drying oven, and dried at a temperature of 50°C for 3h to obtain graphene oxide; Step S12: 0.1 g of graphene oxide and 100 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 40 min at an ultrasonic frequency of 35 kHz, then 0.3 g of ascorbic acid was added and stirred for reaction at a temperature of 0°C and a stirring rate of 300 r / min for 3 h, then the temperature was raised to reflux and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was centrifuged, and the precipitate was immersed in distilled water for 72 h, and then freeze-dried to obtain graphene aerogel; Step S13: 0.1 g of graphene aerogel and 10 mL of hydrofluoric acid with a mass fraction of 10% are added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of -5°C and a stirring rate of 300 r / min for 20 minutes, then the temperature is raised to reflux and the stirring reaction is continued for 20 hours. After the reaction is completed, the reaction product is centrifuged, and the precipitate is immersed in distilled water for 20 hours, and then freeze-dried to obtain fluorine-doped graphene aerogel; Step S14: weigh 35 parts of low-carbon ferrochrome, 8 parts of low-carbon ferromanganese, 7.5 parts of nickel powder, 5 parts of molybdenum powder, 2.5 parts of fluorine-doped graphene aerogel, 4 parts of titanium dioxide, 5 parts of ferrosilicon, 1 part of magnesium oxide, 1 part of yttrium oxide and 22 parts of iron powder according to weight parts, and set aside; Step S15: fully stirring micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, fluorine-doped graphene aerogel, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder, and then wet-milling them, and then placing them in a vacuum drying oven and drying them at a temperature of 130° C. for 3 hours to obtain welding wire powder; Step S16: Roll the C4 steel strip and E304L steel strip to form a U-shaped steel strip, then fill the welding wire powder into the U-shaped steel strip, then roll the U-shaped steel strip closed to form an O-shaped filling steel wire, then draw the O-shaped filling steel wire until the diameter is 1.4 mm, then coil and package to obtain an arc welding flux-cored wire based on C4 steel.

[0016] Embodiment 2: This embodiment is a method for preparing an arc welding flux-cored wire based on C4 steel, comprising the following steps: Step S21: 3 g of flake graphite, 85 mL of 98% concentrated sulfuric acid and 2.5 g of sodium nitrate are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of -3 ° C and a stirring rate of 350 r / min for 25 min, then 14 g of potassium permanganate is added and the stirring reaction is continued for 2 h, then the temperature is raised to 38 ° C and the stirring reaction is continued for 2.5 h, then 135 mL of deionized water is added and the stirring reaction is continued for 11 min, then the temperature is raised to 98 ° C and the stirring reaction is continued for 1.5 h, the reaction is completed and the reaction product is cooled to room temperature, then 18 mL of 30% hydrogen peroxide solution is added, then it is allowed to stand for 2.5 h, then centrifuged, the precipitate is washed with distilled water 4 times in sequence, then placed in a vacuum drying oven, and dried at a temperature of 52 ° C for 4 h to obtain graphene oxide; Step S22: 0.3 g of graphene oxide and 110 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 45 min at an ultrasonic frequency of 40 kHz, then 0.6 g of ascorbic acid was added and stirred for 4 h at a temperature of 3 ° C and a stirring rate of 350 r / min, then the temperature was raised to reflux and the stirring reaction was continued for 12 h. After the reaction was completed, the reaction product was centrifuged, and the precipitate was immersed in distilled water for 84 h, and then freeze-dried to obtain a graphene aerogel; Step S23: 0.3 g of graphene aerogel and 11 mL of hydrofluoric acid with a mass fraction of 12% were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction for 25 min at a temperature of -3 ° C and a stirring rate of 350 r / min, and then the temperature was raised to reflux and the stirring reaction was continued for 22 h. After the reaction was completed, the reaction product was centrifuged, and the precipitate was immersed in distilled water for 25 h, and then freeze-dried to obtain fluorine-doped graphene aerogel; Step S24: weigh 38 parts of low-carbon ferrochrome, 10 parts of low-carbon ferromanganese, 9.5 parts of nickel powder, 7 parts of molybdenum powder, 6 parts of fluorine-doped graphene aerogel, 6 parts of titanium dioxide, 9 parts of ferrosilicon, 2 parts of magnesium oxide, 2 parts of yttrium oxide and 29 parts of iron powder according to weight parts, and set aside; Step S25: fully stirring the micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, fluorine-doped graphene aerogel, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder, and then wet-milling them, and then placing them in a vacuum drying oven and drying them at a temperature of 140° C. for 4 hours to obtain welding wire powder; Step S26: Roll the C4 steel strip and E304L steel strip to form a U-shaped steel strip, then fill the welding wire powder into the U-shaped steel strip, then roll the U-shaped steel strip closed to form an O-shaped filling steel wire, then draw the O-shaped filling steel wire until the diameter is 1.4 mm, then coil and package to obtain an arc welding flux-cored wire based on C4 steel.

[0017] Embodiment 3: This embodiment is a method for preparing an arc welding flux-cored wire based on C4 steel, comprising the following steps: Step S31: Add 3g of flake graphite, 90mL of concentrated sulfuric acid with a mass fraction of 98% and 3g of sodium nitrate to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 30min at a temperature of 0°C and a stirring rate of 400r / min, then add 16g of potassium permanganate and continue stirring and reacting for 2.5h, then heat to 40°C and continue stirring and reacting for 3h, then add 150mL of deionized water and continue stirring and reacting for 12min, then heat to 100°C and continue stirring and reacting for 2h, after the reaction is completed, cool the reaction product to room temperature, then add 20mL of hydrogen peroxide solution with a mass fraction of 30%, then let it stand for 3h, then centrifuge, wash the precipitate with distilled water 5 times in sequence, then place it in a vacuum drying oven, and dry it at a temperature of 55°C for 5h to obtain graphene oxide; Step S32: 0.5 g of graphene oxide and 120 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 50 min at an ultrasonic frequency of 45 kHz, then 0.9 g of ascorbic acid was added and stirred for reaction at a temperature of 5° C. and a stirring rate of 400 r / min for 5 h, then the temperature was raised to reflux and the stirring reaction was continued for 15 h. After the reaction was completed, the reaction product was centrifuged, and the precipitate was immersed in distilled water for 96 h, and then freeze-dried to obtain graphene aerogel; Step S33: adding 0.5 g of graphene aerogel and 12 mL of hydrofluoric acid with a mass fraction of 15% into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stirring the reaction for 30 min at a temperature of 0°C and a stirring rate of 400 r / min, then heating to reflux and continuing to stir the reaction for 25 h, centrifuging the reaction product after the reaction is completed, immersing the precipitate in distilled water for 30 h, and then freeze-drying to obtain fluorine-doped graphene aerogel; Step S34: weigh 40 parts of low-carbon ferrochrome, 12 parts of low-carbon ferromanganese, 11.5 parts of nickel powder, 9 parts of molybdenum powder, 9.5 parts of fluorine-doped graphene aerogel, 8 parts of titanium dioxide, 13 parts of ferrosilicon, 3 parts of magnesium oxide, 3 parts of yttrium oxide and 36 parts of iron powder according to weight parts, and set aside; Step S35: fully stirring micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, fluorine-doped graphene aerogel, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder, then wet-milling, and then placing in a vacuum drying oven and drying at a temperature of 150° C. for 5 hours to obtain welding wire powder; Step S36: Roll the C4 steel strip and E304L steel strip to form a U-shaped steel strip, then fill the welding wire powder into the U-shaped steel strip, then roll the U-shaped steel strip closed to form an O-shaped filling steel wire, then draw the O-shaped filling steel wire until the diameter is 1.4 mm, then coil and package to obtain an arc welding flux-cored wire based on C4 steel.

[0018] Comparative Example 1: This comparative example is a method for preparing an arc welding flux-cored wire based on C4 steel, comprising the following steps: Step D11: Weigh 40 parts of low-carbon ferrochrome, 12 parts of low-carbon ferromanganese, 11.5 parts of nickel powder, 9 parts of molybdenum powder, 8 parts of titanium dioxide, 13 parts of ferrosilicon, 3 parts of magnesium oxide, 3 parts of yttrium oxide and 36 parts of iron powder according to weight parts, and set aside; Step D12: fully stir the micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder, then wet-mill them, and then place them in a vacuum drying oven and dry them at a temperature of 150° C. for 5 hours to obtain welding wire powder; Step D13: Roll the C4 steel strip and E304L steel strip to form a U-shaped steel strip, then fill the welding wire powder into the U-shaped steel strip, then roll the U-shaped steel strip closed to form an O-shaped filling steel wire, then draw the O-shaped filling steel wire until the diameter is 1.4 mm, and then coil and package it to obtain an arc welding flux-cored wire based on C4 steel.

[0019] Comparative Example 2: This comparative example is a method for preparing an arc welding flux-cored wire based on C4 steel, comprising the following steps: Step D21: Add 3g of flake graphite, 90mL of concentrated sulfuric acid with a mass fraction of 98% and 3g of sodium nitrate to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 30min at a temperature of 0°C and a stirring rate of 400r / min, then add 16g of potassium permanganate and continue stirring and reacting for 2.5h, then heat to 40°C and continue stirring and reacting for 3h, then add 150mL of deionized water and continue stirring and reacting for 12min, then heat to 100°C and continue stirring and reacting for 2h, after the reaction is completed, cool the reaction product to room temperature, then add 20mL of hydrogen peroxide solution with a mass fraction of 30%, then let it stand for 3h, then centrifuge, wash the precipitate with distilled water 5 times in sequence, then place it in a vacuum drying oven, and dry it at a temperature of 55°C for 5h to obtain graphene oxide; Step D22: Weigh 40 parts of low-carbon ferrochrome, 12 parts of low-carbon ferromanganese, 11.5 parts of nickel powder, 9 parts of molybdenum powder, 9.5 parts of graphene oxide, 8 parts of titanium dioxide, 13 parts of ferrosilicon, 3 parts of magnesium oxide, 3 parts of yttrium oxide and 36 parts of iron powder according to weight parts, and set aside; Step D23: fully stirring micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, graphene oxide, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder, and then wet-milling them, and then placing them in a vacuum drying oven and drying them at a temperature of 150° C. for 5 hours to obtain welding wire powder; Step D24: Roll the C4 steel strip and E304L steel strip to form a U-shaped steel strip, then fill the welding wire powder into the U-shaped steel strip, then roll the U-shaped steel strip closed to form an O-shaped filling steel wire, then draw the O-shaped filling steel wire until the diameter is 1.4 mm, and then coil and package it to obtain an arc welding flux-cored wire based on C4 steel.

[0020] Comparative Example 3: This comparative example is a method for preparing an arc welding flux-cored wire based on C4 steel, comprising the following steps: Step D31: Add 3 g of flake graphite, 90 mL of 98% concentrated sulfuric acid and 3 g of sodium nitrate to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 30 min at 0 ° C and a stirring rate of 400 r / min, then add 16 g of potassium permanganate and continue stirring and reacting for 2.5 h, then heat to 40 ° C and continue stirring and reacting for 3 h, then add 150 mL of deionized water and continue stirring and reacting for 12 min, then heat to 100 ° C and continue stirring and reacting for 2 h, after the reaction is completed, cool the reaction product to room temperature, then add 20 mL of 30% hydrogen peroxide solution, then let it stand for 3 h, then centrifuge, wash the precipitate with distilled water 5 times in sequence, then place it in a vacuum drying oven, and dry it at 55 ° C for 5 h to obtain graphene oxide; Step D32: 0.5 g of graphene oxide and 120 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersed for 50 min at an ultrasonic frequency of 45 kHz, then 0.9 g of ascorbic acid was added and stirred for reaction at a temperature of 5° C. and a stirring rate of 400 r / min for 5 h, then the temperature was raised to reflux and the stirring reaction was continued for 15 h. After the reaction was completed, the reaction product was centrifuged, and the precipitate was immersed in distilled water for 96 h, and then freeze-dried to obtain graphene aerogel; Step D33: Weigh 40 parts of low-carbon ferrochrome, 12 parts of low-carbon ferromanganese, 11.5 parts of nickel powder, 9 parts of molybdenum powder, 9.5 parts of graphene aerogel, 8 parts of titanium dioxide, 13 parts of ferrosilicon, 3 parts of magnesium oxide, 3 parts of yttrium oxide and 36 parts of iron powder according to weight parts, and set aside; Step D34: fully stir the micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, graphene aerogel, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder, then wet-mill them, and then place them in a vacuum drying oven and dry them at a temperature of 150° C. for 5 hours to obtain welding wire powder; Step D35: Roll the C4 steel strip and E304L steel strip to form a U-shaped steel strip, then fill the welding wire powder into the U-shaped steel strip, then roll the U-shaped steel strip closed to form an O-shaped filling steel wire, then draw the O-shaped filling steel wire until the diameter is 1.4 mm, and then coil and package it to obtain an arc welding flux-cored wire based on C4 steel.

[0021] The arc welding flux-cored welding wires based on C4 steel of Examples 1-3 and Comparative Examples 1-3 were subjected to surfacing experiments with C4 steel plates as base materials. The welding parameters were: welding current 190A, arc voltage 28V, welding speed 10m / h, and nitrogen and argon mixed gas flow rate of 1-1.5L / min. The deposited metal was then subjected to performance tests. The test results are shown in the following table:

[0022] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the addition of fluorine-doped graphene aerogel significantly improves the nitric acid corrosion resistance and mechanical properties of the arc welding flux-cored wire based on C4 steel.

[0023] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0024] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An arc welding flux-cored wire based on C4 steel, characterized in that: Including welding wire coating layer and welding wire powder; The welding wire coating layer is an E304L steel strip with a thickness of 0.3 mm; The mass of the welding wire powder is 28% of the mass of the arc welding flux-cored wire based on C4 steel; Wherein, the welding wire powder comprises the following components in parts by weight: 35-40 parts of micro-carbon ferrochrome, 8-12 parts of low-carbon ferromanganese, 7.5-11.5 parts of nickel powder, 5-9 parts of molybdenum powder, 2.5-9.5 parts of fluorine-doped graphene aerogel, 4-8 parts of titanium dioxide, 5-13 parts of ferrosilicon, 1-3 parts of magnesium oxide, 1-3 parts of yttrium oxide and 22-36 parts of iron powder; Wherein, the fluorine-doped graphene aerogel is prepared by the following steps: Step s1: adding flake graphite, concentrated sulfuric acid and sodium nitrate to a three-necked flask equipped with an agitator and a thermometer, stirring the reaction at a temperature of -5-0°C and a stirring rate of 300-400r / min for 20-30min, then adding potassium permanganate and continuing to stir the reaction for 1.5-2.5h, then heating to 35-40°C and continuing to stir the reaction for 2-3h, then adding deionized water and continuing to stir the reaction for 10-12min, then heating to 95-100°C and continuing to stir the reaction for 1-2h, after the reaction is completed, the reaction product is cooled to room temperature, then hydrogen peroxide solution is added, then allowed to stand for 2-3h, then centrifuged, the precipitate is washed with distilled water for 3-5 times in sequence, then placed in a vacuum drying oven, and dried at a temperature of 50-55°C for 3-5h to obtain graphene oxide; Step s2: adding graphene oxide and deionized water to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and ultrasonically dispersing for 40-50 minutes at an ultrasonic frequency of 35-45kHz, then adding ascorbic acid and stirring the mixture for 3-5 hours at a temperature of 0-5°C and a stirring rate of 300-400r / min, then heating the mixture to reflux and continuing to stir the mixture for 10-15 hours, centrifuging the reaction product after the reaction is completed, and immersing the precipitate in distilled water for 72-96 hours, and then freeze-drying the mixture to obtain graphene aerogel; Step s3: Add graphene aerogel and hydrofluoric acid into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 20-30 minutes at a temperature of -5-0°C and a stirring rate of 300-400r / min, then raise the temperature to reflux and continue stirring and reacting for 20-25 hours. After the reaction is completed, centrifuge the reaction product, immerse the precipitate in distilled water for 20-30 hours, and then freeze-dry to obtain fluorine-doped graphene aerogel.

2. The arc welding flux-cored wire based on C4 steel according to claim 1, characterized in that: The usage ratio of the flake graphite, concentrated sulfuric acid, sodium nitrate, potassium permanganate, deionized water and hydrogen peroxide solution in step s1 is 3g:80-90mL:2-3g:12-16g:120-150mL:15-20mL.

3. The arc welding flux-cored wire based on C4 steel according to claim 1, characterized in that: The mass fraction of the concentrated sulfuric acid in step s1 is 98%; the mass fraction of the hydrogen peroxide solution is 30%.

4. The flux-cored arc welding wire based on C4 steel according to claim 1, characterized in that: The usage ratio of the graphene oxide, deionized water and ascorbic acid in step s2 is 0.1-0.5 g:100-120 mL:0.3-0.9 g.

5. The flux-cored arc welding wire based on C4 steel according to claim 1, characterized in that: The usage ratio of the graphene aerogel and hydrofluoric acid in step s3 is 0.1-0.5 g: 10-12 mL.

6. The flux-cored arc welding wire based on C4 steel according to claim 1, characterized in that: The mass fraction of the hydrofluoric acid in step s3 is 10-15%.

7. A method for preparing an arc welding flux-cored wire based on C4 steel as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Weigh 35-40 parts of low-carbon ferrochrome, 8-12 parts of low-carbon ferromanganese, 7.5-11.5 parts of nickel powder, 5-9 parts of molybdenum powder, 2.5-9.5 parts of fluorine-doped graphene aerogel, 4-8 parts of titanium dioxide, 5-13 parts of ferrosilicon, 1-3 parts of magnesium oxide, 1-3 parts of yttrium oxide and 22-36 parts of iron powder according to weight parts, and set aside; Step 2: fully stir micro-carbon ferrochrome, low-carbon ferromanganese, nickel powder, molybdenum powder, fluorine-doped graphene aerogel, titanium dioxide, ferrosilicon, magnesium oxide, yttrium oxide and iron powder, then wet-mill them, and then place them in a vacuum drying oven and dry them at a temperature of 130-150° C. for 3-5 hours to obtain welding wire powder; Step 3: Roll the E304L steel strip to form a U-shaped steel strip, then fill the welding wire powder into the U-shaped steel strip, then roll the U-shaped steel strip closed to form an O-shaped filling steel wire, then draw the O-shaped filling steel wire until the diameter is 1.4 mm, then coil and package to obtain an arc welding flux-cored wire based on C4 steel.

Citation Information

Patent Citations

  • High-wear-resistance nickel-based alloy flux-cored wire and preparation method thereof

    CN116329802A

  • Special stainless steel flux-cored wire for enhancing welding strength of C4 steel and preparation method of special stainless steel flux-cored wire

    CN118237796A

  • Flux cored wire

    RU2825974C1

  • Flux for welding aluminium alloys

    SU1138283A1